A Systematic Literature Review of Online Shopping in Sports Goods and Ser-vices: Considering the Role of Trust and Perceived Risk - Houriyhe Dehghanpouri (Research in Sport Management and Marketing)
Purpose: This paper reviews and discusses recent literature on trust, perceived risk and behavioral intention in online shopping for sports products and services. On this basis, we propose a hypothetical model as a basis for theoretical and hypothetical development in future research.Methods: The paper complies with the methodological requirements of Systematic Literature Reviews (SLR). The current SLR gathers and synthesizes research records of the last 13 years (2007–May2020) on consumer perceived risks, trust and concerning behavioral intention in online shopping in sport domain. Online stores selling sporting goods and services should take into deterrents and risk factors to increase their sales, keeping existing customers and attracting new customers and their trust. One of the suggested solutions for this purpose is create a website that consumers enable easily evaluate products and services also minimized perceived risk. In addition, the results hold important implications in the areas of segmentation and targeting decisions.Results: In practical terms, our research findings imply that building trust and reducing perceived risk are important for online shopping for sports products and services Therefore, the sporting goods online providers need a better understanding of users’ perceptions concerning the services and goods.Conclusion: A trust of website multidimensional nature makes it a very useful and essential intention to purchase tool. Therefore, it provides beneficial results for the organization's managers to study the important factors affecting it. Also, results offer a better understanding of customer intent to online buying sports products. Our synthesis provides a detailed account of the perceived risk factors, their antecedents and consequences, risk‐reducing strategies, and future research potential in the said domain.